2013
DOI: 10.4040/jkan.2013.43.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Update on Irritable Bowel Syndrome Program of Research

Abstract: Purpose: This article provides an update and overview of a nursing research program focused on understanding the pathophysiology and management of irritable bowel syndrome (IBS). Methods: This review includes English language papers from the United States, Europe, and Asia (e.g., South Korea) from 1999 to 2013. We addressed IBS as a health problem, emerging etiologies, diagnostic and treatment approaches and the importance of a biopsychosocial model. Results: IBS is a chronic, functional gastrointestinal disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…It was found that there is an increased IBS risk among the first, second, and third-degree relatives from a Swedish population. Genetic factors may also contribute to the patho-physiology, which indicates a genetic component of the familial clustering of IBS (40). These studies correlate with results obtained among medical students.…”
Section:  Familial Factorssupporting
confidence: 79%
See 1 more Smart Citation
“…It was found that there is an increased IBS risk among the first, second, and third-degree relatives from a Swedish population. Genetic factors may also contribute to the patho-physiology, which indicates a genetic component of the familial clustering of IBS (40). These studies correlate with results obtained among medical students.…”
Section:  Familial Factorssupporting
confidence: 79%
“… Sleep disorder IBS patients were generally reported to have poor sleep (40). It was postulated that poor sleep is a dangerous stress factor which can seriously influence gastrointestinal function, cognition, emotion, and somatic reaction.…”
Section: C) Obesitymentioning
confidence: 99%
“…Inflammation is known to affect IBS. 46 However, we found no significant difference in the potential factor among the SCTs (e.g., hsCRP [ Table 1]). Stress response to psychological stress can also be a possible mediator for the relationship.…”
Section: Discussionmentioning
confidence: 79%
“…Irritable bowel syndrome-constipation (IBS-C) is a type of IBS characterized by abdominal pain or discomfort, lumpy/ hard stools, and abnormal stool passage (straining, or feeling of incomplete evacuation) (2,3). Although the pathophysiology of constipation is multifactorial and not yet fully understood, considerable evidence supports involvement of the microbiome, immune function, diet, genetics, psychological distress, and recent environmental stress as contributing factors (4).…”
mentioning
confidence: 99%